Α‐Synuclein in blood cells differentiates Parkinson's disease from healthy controls. Issue 12 (19th November 2019) - Abd Elhadi, Suaad; Grigoletto, Jessica; Poli, Maura; Arosio, Paolo; Arkadir, David; Sharon, Ronit
Abstract: Objective: To determine whether blood cells expressed α‐Syn can differentiate Parkinson's disease (PD) from healthy controls (HC). Methods: The concentrations of α‐Syn were determined in samples of blood cell pellets using a quantitative Lipid‐ELISA assay. In addition, the levels of total protein, hemoglobin, iron and H‐ferritin were determined. The study includes samples from the Biofind cohort ( n = 46 PD and 45 HC) and results were validated with an additional cohort ( n = 35 PD and 28 HC). Results: A composite biomarker consisting of the concentrations of total α‐Syn, proteinase‐K resistant (PK res ) α‐Syn and phospho‐Serine 129 α‐Syn (PSer 129), is designed based on the analysis of the discovery BioFIND cohort. This composite biomarker differentiates a PD subgroup, presenting motor symptoms without dementia from a HC group, with a convincing accuracy, represented by an AUC = 0.81 (95% CI, 0.71 to 0.92). Closely similar results were obtained for the validation cohort, that is, AUC = 0.81, (95% CI, 0.70 to 0.94). Interpretation: Our results demonstrate the potential usefulness of blood cells expressed α‐Syn as a biomarker for PD.